1980
DOI: 10.1007/bf02242613
|View full text |Cite
|
Sign up to set email alerts
|

Crossbreeding in tropical sheep: Incidence of dystocia and parturition losses

Abstract: Studies were carried out on the incidence of dystocia and parturition losses during a crossbreeding experiment involving 96 West African Dwarf (WAD) ewes mated with rams of 4 breeds--WAD, Ouda, Permer and Yankassa. Results obtained indicated 8 (5.7%) cases of dystocia and 20 (10.64%) cases of stillbirths or death of lambs at birth. The WAD sires were not associated with dystocia or stillbirths but other sire groups were involved in both. All the difficult parturitions occurred during the rainy season while all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…It seems that this inflectionary period in the growth rate of WAD foetuses is crucial in any feed supplementation programmes during pregnancy. It also indicates that unnecessarily high feed supplementation during this period should be avoided to minimize obstetrical problems as a high level of nutrition in small ruminants has been associated with dystocia (MONLE, 1964;OSUAGWUH et al, 1980).…”
Section: Fig 1 Growth Rate Per Day Of Gestation Of the Foetus Of Wementioning
confidence: 99%
See 1 more Smart Citation
“…It seems that this inflectionary period in the growth rate of WAD foetuses is crucial in any feed supplementation programmes during pregnancy. It also indicates that unnecessarily high feed supplementation during this period should be avoided to minimize obstetrical problems as a high level of nutrition in small ruminants has been associated with dystocia (MONLE, 1964;OSUAGWUH et al, 1980).…”
Section: Fig 1 Growth Rate Per Day Of Gestation Of the Foetus Of Wementioning
confidence: 99%
“…Records for small ruminants in the theriogenology clinic of the University of Ibadan indicate a high rate of obstetrical problems due to absolute foetal oversize (OSUAGWUH et al, 1980), neonatal mortality due to maternal malnutrition during pregnancy (OSUAGWUH and AKPOKODJE, 1981) and recently, nutritional abortion (OSUAGWUH and AKPOKODJE, 1986). Nutrition, sire and sex are some of the factors that influence foetal dystocia, abortion and neonatal mortality in farm animals (MONLE, 1964;BELLOWS et al, 1971;OSUAGWUH et al, 1980;AKPOKODJE, 1981, 1986). Since nutrition is essential for foetal survival and growth, and for full phenotypic expression of the sire and sex genetic potentials, it is considered that nutrition of pregnant West African dwarf (Fouta djallon) (WAD) goats may be easier to manipulate to aovid reproductive wastage, than sire and sex factors.…”
Section: Introductionmentioning
confidence: 99%
“…le J f f ta ' f o Z " Jr I H growthisduemoretohypertrophythantohyperplasia W k A D S o a t (Osuagwuh & A™ 1 9 9 0 )-Unpublished as fetal age increases, it has been suggested that observations by Osuagwuh show that there retardation of fetal growth late in gestation should P 0 S 1 ' I v e i n e a r relationship between he crude protein have a less severe effect on subsequent neonatal intake of pregnant WAD does and fetal weight gain, development than retardation at an early stage (Prior T h i s Phenomenon may have obstetric imp .cations & Laster 1979). The literature is scanty on the effects * m c e .^w e i g h t has also been associated wth of supplementary feeding of these animals during ^t o a a ' " J^P (Osuagwuh et a I 1980). The goat gestation based on their known intrauterine growth i n d u s t I 7 i n N l S e n a would benefit ,f does received the pattern.…”
Section: Introductionmentioning
confidence: 99%
“…An unscientific approach to animal feeding, optimal nutritional level, leading neither to abortion especially during pregnancy, may lead to reproductive n o r f e t a l o v e r s i z e -T K he P ™ a r y objective of his study wastage resulting from either dystocia due to absolute w a s t 0 m o n l l°r . t h e e f f e c t s o f * lm^lc f eed SU P" fetal oversize as a result of a high level of feeding plementation during pregnancy based on the known throughout gestation (Osuagwuh et at. 1980) or from 'ntrautenne growth characters ics of the WAD goat, abortion and neonatal death due to low birthweight o n f e t a l birthweight perinatal survival and udder resulting from malnutrition during pregnancy (Osuag-circumference of the does, wuh & Akpokodje 1981, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…This is why early diagnose is important at maternity complications which can lead to serious economic losses. It is considered that many factors such as pelvic size, birth weight of calf, mothers' age, twin pregnancy, presentation defect, hormonal level, nourishment, stress and many other unknown factors affect severe births (Abeni et al, 2004;Oakes et al, 2001;Osuagwuh et al, 1980;Roberts 1986). Abortion is defined as removing the fetus, which does not have the chance to live outside, either dead or alive before the pregnancy period is completed.…”
Section: Introductionmentioning
confidence: 99%